1992
DOI: 10.1148/radiology.184.2.1620838
|View full text |Cite
|
Sign up to set email alerts
|

Nonpalpable, probably benign lesions: role of follow-up mammography.

Abstract: Of 21,855 consecutive women prospectively studied with mammography, physical examination, and high-resolution ultrasonography when appropriate, 558 received a diagnosis of nonpalpable, probably benign lesions. Follow-up mammography was recommended for these patients. Characteristically benign lesions and palpable masses were excluded from analysis. The positive predictive value for detection of a nonpalpable, probably benign breast lesion was 0.017. Nine patients ultimately proved to have carcinoma; two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
121
5
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(139 citation statements)
references
References 0 publications
10
121
5
3
Order By: Relevance
“…Furthermore, only lesions that underwent biopsy were included in this study. When we report a 9% frequency of carcinoma in circumscribed masses, for exam ple, this refers to circumscribed masses on which surgical biopsy was performed (usually because of interval growth): it is not surprising that this 9% frequency exceeds the previously reported 1â€"2% frequency of carcinoma in circumscribed masses on a baseline mammogram [8,9]. Inclu sion of only biopsy-proven cases in our study en sw-es histopathologic validation but does not enable us to determine the frequency of carci noma in lesions that are less suggestive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, only lesions that underwent biopsy were included in this study. When we report a 9% frequency of carcinoma in circumscribed masses, for exam ple, this refers to circumscribed masses on which surgical biopsy was performed (usually because of interval growth): it is not surprising that this 9% frequency exceeds the previously reported 1â€"2% frequency of carcinoma in circumscribed masses on a baseline mammogram [8,9]. Inclu sion of only biopsy-proven cases in our study en sw-es histopathologic validation but does not enable us to determine the frequency of carci noma in lesions that are less suggestive.…”
Section: Resultsmentioning
confidence: 99%
“…Inclu sion of only biopsy-proven cases in our study en sw-es histopathologic validation but does not enable us to determine the frequency of carci noma in lesions that are less suggestive. The lat ter question, which was addressed by Sickles [8] andVaraset al [9] beforethepublication of the BI-RADS lexicon, may deserve reinvestigation using BI-RADS terminology.…”
Section: Resultsmentioning
confidence: 99%
“…Potential cases with ages 70 or higher were not taken into account, regarding the lack of healthy controls to match them and also to reduce a possible recall bias. Their recruitment was performed in patients with mamographically BI-RADS 4 (suspicious of malignancy) and 5 (highly suspicious of cancer) lesions (Varas et al, 1992;Feig, 1999), and a positive cytologic (on site) study, which was furtherly histologically confirmed, according to its high correlation with histopathology (Jaumandreu et al, 2001). Initially, no information on cancer stage was collected through the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Cytology was performed on biopsies of breast tissue obtained from patients who were classified as BIRADS categories 4 (suspicious of malignancy) and 5 (positive diagnosis of cancer) (Varas, 1992; American College of Radiology, 1998) on the basis of their mammogram. Since BC cases were interviewed and measured very soon, they have not experienced any post-diagnostic or treatment-induced weight change.…”
Section: Methodsmentioning
confidence: 99%